Strategi Penerapan Pembelajaran Audiovisual untuk Mengembangkan Minat Belajar Anak Usia 5-6 Tahun di TK Gotong Royong Krampon - Putri, Nur Fransiska Maulidia; Salim, Agus (Universitas Nusantara PGRI Kediri, 2025)
Teachers at the Mutual Cooperation Krampon Kindergarten use audiovisual media twice a week. The main purpose of using media is to attract children's attention and make learning easier and easier to understand. Data collection used observation, interviews and documentation to obtain and collect audiovisual data on implementation at Mutual Cooperation Kindergarten 1 Krampon. The interviews used included sources of information as well as teachers and students. The research uses the Miles and Huberman analytical data model. Namely data collection, reduction, presentation and verification. After the teacher gives the video to the child, they give instructions to the child to retell the video. After the video is shown, the child begins to develop. As the child watches the video over and over again, he begins to improve. First video to end of video. The results show a video about introducing the concept of numbers and letters using an animated video that is interesting and easy for children to follow, active involvement in questions and answers and discussions and being able to recognize animal sounds. With interesting characters, it helps children be more focused and enthusiastic. This can be seen from the children's enthusiasm in carrying out assignments after being exposed to the topic through audio-visual media. There, their assignments are always linked to each lesson, making them very enthusiastic and able to do their assignments well independently.